Tinjauan Kriminologi Pekerja Seks Komersial Pasca Penutupan Karang Dempel (KD) di Kelurahan Alak Kota Kupang - Meylischa Irna Lamma; Rudepel Petrus Leo; Rosalind Angel Fanggi (Lembaga Pengembangan Kinerja Dosen, 2024)
In today's developments, especially in Indonesia, many criminal acts are increasing. One of the cases of crime in Indonesia that is high among women is prostitution. The act of prostitution is strictly prohibited in Indonesia because prostitution is an act of crime against morality and is against the law and is against human rights and also falls within the scope of the field of criminology. This research is empirical juridical research. The data collected was taken from primary and secondary data which was then analyzed descriptively qualitatively. The research results show that: (1) The factors causing prostitutes to still operate in Karang Dempel consist of Economic factors, Lifestyle Factors, Social Environmental Factors, Educational Factors, Legal Factors. (2) Law enforcement efforts to deal with prostitutes who are still operating in Karang Dempel consist of pre-emptive efforts, namely prevention so that crimes do not occur, preventive efforts, namely action carried out by authorized officers in accordance with statutory regulations and repressive efforts, namely efforts that carried out to take action against criminals according to their actions. Based on the problem of prostitution, it is recommended that law enforcement officers provide more guidance or outreach to local residents so that they are more aware of the impact of prostitution, especially for teenagers, in order to provide a deterrent effect on perpetrators of prostitution and not doing it again. It is hoped that the local government will continue to monitor the area of ​​prostitution in the hope that the government's promises regarding financial assistance and business assistance can be allocated to create harmony.